2015
DOI: 10.1016/j.molp.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Phenotyping System and Analytics Platform Reveals Diverse Temporal Responses to Water Availability in Setaria

Abstract: Phenotyping has become the rate-limiting step in using large-scale genomic data to understand and improve agricultural crops. Here, the Bellwether Phenotyping Platform for controlled-environment plant growth and automated multimodal phenotyping is described. The system has capacity for 1140 plants, which pass daily through stations to record fluorescence, near-infrared, and visible images. Plant Computer Vision (PlantCV) was developed as open-source, hardware platform-independent software for quantitative imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
289
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(310 citation statements)
references
References 72 publications
5
289
0
2
Order By: Relevance
“…Commonly used growth curve models (sigmoidal curves) generally require data from across the entire life cycle of the plant, which can limit the types of phenotyping data to which these models can be applied. For example, many greenhouse or ground-based phenotyping systems can only be employed to gather data from plants below a fixed height limit 8,9 . For taller crops such as maize or bioenergy sorghum, only a portion of the lifecycle can be phenotyped without exceeding these height limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used growth curve models (sigmoidal curves) generally require data from across the entire life cycle of the plant, which can limit the types of phenotyping data to which these models can be applied. For example, many greenhouse or ground-based phenotyping systems can only be employed to gather data from plants below a fixed height limit 8,9 . For taller crops such as maize or bioenergy sorghum, only a portion of the lifecycle can be phenotyped without exceeding these height limits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the UNL Greenhouse Innovation Center has the capacity to image approximate 400 plants per day, while significantly more total plants can be grown in parallel 17 . Similar systems such as the Bellweather phenotyping system also have the capacity to grow more plants simultaneously than can be imaged over the course of a single day 9 . Phenotypes collected from unmanned aerial vehicles (UAVs) suffer from a similar constraint on how many plots can be imaged per day, with the additional constraint that unsuitable weather conditions -high wind, thunderstorms etc -can result in missing data from particular sites on particular dates, producing unbalanced final phenotypic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial platforms, including the Scanalyzer series from Lemnatec (http:// www.lemnatec.com/products/; accessed February 2016) and the Traitmill platform from CropDesign (http:// www.cropdesign.com/general.php; accessed February 2016), have gained adoption in the research community and have promoted the development of additional software (beyond that which the respective companies provide) to analyze the images produced by the platform (Reuzeau, 2007;Hartmann et al, 2011;Fahlgren et al, 2015a). A variety of noncommercial platforms and methods developed by the research community also exist and have been demonstrated to perform well (White et al, 2012;Fiorani and Schurr, 2013;Sirault et al, 2013;Pound et al, 2014).…”
mentioning
confidence: 99%
“…Therefore, we used the segmented plant images as the input of our system. We propose a plant object segmentation method based on the PlantCV (Plant Computer Vision) suite [23]. This is an open source platform to which multiple research teams, including ours, are contributing.…”
Section: Plant Object Segmentation Based On Plantcvmentioning
confidence: 99%